Piip, Meierovics & Voldemaras, Estonia, Latvia & Lithuania : Makers of the Modern World. - Alston, Charlotte (Makers of the Modern World., 2011)
A history of the Baltic states, from Versailles, through World War II, to Soviet occupation.